The high-risk HPV oncogene E7 upregulates miR-182 expression through the TGF-β/Smad pathway in cervical cancer. (28th September 2019) - Chen, Jiao; Deng, Yan; Ao, Liangfei; Song, Yi; Xu, Yan; Wang, Chi Chiu; Choy, Kwong Wai; Tony Chung, Kwok Hung; Du, Quan; Sui, Yi; Yang, Tao; Yang, Jing; et al.
Abstract: Accumulating experimental evidence has shown that the aberrant expression of microRNAs (miRNAs) is involved in the development and progression of human cervical cancer. Previously, we identified miR-182 as an oncomiRNA in cervical cancer. However, the mechanism by which miR-182 is regulated and the interaction between human papillomavirus (HPV) and miR-182 in cervical cancer development remains unknown. In the present study, we explored the link between HPV E7 and miR-182 and verified that high-risk HPV E7 upregulated miR-182 expression through TGF-β/Smad4 signaling pathway in cervical cancer. By contrast, low-risk HPV E7 did not affect the expression of TGF-β and miR-182. Mechanistically, as high-risk HPV E7 bound to pRb, E2F was released from the complex and bound to the TGF-β promoter region, resulting in TGF-β overexpression. Furthermore, the Smad4 signaling pathway was activated upon TGF-β overexpression, which led to an interaction between Smad4 and the miR-182 promoter region, subsequently inducing the upregulation of miR-182 in both cervical cancer cells and the surrounding normal cells. In conclusion, this newly identified high-risk HPV E7/TGF-β/miR-182 regulatory network might inform the development of specific therapeutic strategies for cervical cancer. Highlights: High-risk HPV E7 upregulated miR-182 expression through TGF-β/Smad4 signaling pathway in cervical cancer. Low-risk HPV E7 did not affect the expression of TGF-β and miR-182 in cervical cancer cells. Cervical cancer cells induce surrounding normal cells to express TGF-β and miR-182.